Self‐Assembly and Fluorescence of Tetracationic Liquid Crystalline Tetraphenylethene. Issue 17 (31st July 2019) - Knelles, Jakob; Beardsworth, Stuart; Bader, Korinna; Bruckner, Johanna R.; Bühlmeyer, Andrea; Forschner, Robert; Schweizer, Kevin; Frey, Wolfgang; Giesselmann, Frank; Molard, Yann; Laschat, Sabine
Abstract: A series of tetraguanidinium tetraphenylethene (TPE) arylsulfonates with different chain lengths was prepared via ionic self‐assembly of tetraguanidinium TPE chloride and the respective methyl arylsulfonates. Liquid crystalline properties were studied by differential scanning calorimetry, polarizing optical microscopy and X‐ray diffraction. Tetraguanidinium TPE arylsulfonates with chain lengths of C8 –C12 displayed hexagonal columnar mesophases over a broad temperature range, while derivatives with longer chains showed oblique columnar phases. In solution all compounds displayed aggregation‐induced emission behaviour. Temperature‐dependent luminescence spectra of the bulk phase of the tetraguanidinium TPE arylsulfonate with C14 side chains revealed a strong luminescence both in the solid state and the oblique columnar mesophase. The emission behaviour was rationalized by a unique combination of restriction of intramolecular rotation of the TPE core, Coulomb interaction between the guanidinium cations and π–π interactions of the anionic arylsulfonate moieties. Abstract : Aggregation matters : the self‐assembly of ionic‐liquid crystals based on tetracationic tetraphenylethene and arylsulfonate counterions results in stable columnar mesophases and strong fluorescence emission both in the bulk mesophase as well as in concentrated solution. X‐ray diffraction studies provide insight into the mesophase geometries, revealing hexagonal columnar phases for tetraphenylethene ionic‐liquid crystals with side‐chain lengths of C8 –C12 and oblique columnar phases for derivatives with C14 –C16 chains.